PENGARUH PENYULUHAN DENGAN FILM ANIMASI TERHADAP PENGETAHUAN SISWA SDN 70 KENDARI TENTANG CUCI TANGAN - Purnamasari, Anisa; Zoahira, Wa Ode Aisa; Yusnayanti, Cici; Lisnawati, Lisnawati; Romantika, I Wayan; Andas, Amzal Mortin (Program Studi S1/DIII-Keperawatan Universitas Imelda Medan, 2023)
Background The World Health Organization (WHO) designated COVID-19 as a Pandemic. Hand washing behavior using soap is an effort that has a major impact in preventing infectious diseases such as diarrhea and ARI, as well as a Preventive Effort in Breaking the Chain of COVID-19 Spread, but hand washing is still not a habit in society, especially children. The purpose of this study was to determine the effect of counseling through animated film media on increasing students' knowledge about handwashing behavior with soap as a preventive effort in breaking the chain of the spread of COVID-19. Method This research is Pre-Experimental using the One group Pretest-Posttest Design without a control group. This research was conducted at SDN 70 Kendari in April 2021, while the instrument used was a questionnaire made by researchers. The population in this study was 182 students. The sampling technique used consecutive sampling with a total sample size of 120 students. Results The t-value is -22.514 with a p value of 0.000 <0.05 so it can be concluded that there is an effect of counseling through animated film media on increasing student knowledge about hand washing with soap behavior as a preventive effort in breaking the chain of COVID-19 spread. Conclusion There is an Effect of Counseling Through Animated Film Media on Increasing Student Knowledge Regarding Handwashing Behavior Using Soap as a Preventive Effort in Breaking the Chain of COVID-19 Spread.